'Greater Chinese' Global Production Networks in the Middle East: The Rise of the Jordanian Garment Industry. Issue 6 (4th November 2013) - Azmeh, Shamel; Nadvi, Khalid
ABSTRACT: The expansion of 'Greater Chinese' capital from mainland China, Hong Kong and Taiwan into other parts of the developing world is increasingly noted. It is especially prominent in sub‐Saharan Africa where Greater Chinese investments, firms and workers are found across a wide range of activities, from the extractive commodity sectors, to infrastructure projects, agriculture and manufacturing. One region where Greater Chinese investment is less well studied is the Middle East. This article focuses on the case of Jordan. Jordan has rapidly emerged as an important supplier of apparel to the United States, a consequence of a distinct preferential trade agreement. The article charts the ways in which this preferential trade agreement has stimulated the shifts of Greater Chinese garment manufacturers to Jordan. Using a global production networks (GPN) framework, and drawing on primary and secondary evidence, it assesses the dynamics behind Greater Chinese investments into Jordan; it also explores the ways in which Greater Chinese garment producers operating in Jordan organize their supply chains and are linked into the global garments GPNs. Finally, it considers the relationship between such capital flows and the influx of Asian migrant workers into the Jordanian export garment sector.